Interannual comparison of core taxa and community composition of the blow microbiota from East Australian humpback whales. Issue 8 (1st July 2019) - Vendl, C; Ferrari, B C; Thomas, T; Slavich, E; Zhang, E; Nelson, T; Rogers, T
ABSTRACT: Cetacean represent vulnerable species impacted by multiple stressors, including reduction in prey species, habitat destruction, whaling and infectious disease. The composition of blow microbiota has been claimed to provide a promising tool for non-invasive health monitoring aiming to inform conservation management. Still, little is known about the temporal stability and composition of blow microbiota in whales. We used East Australian humpback whales ( Megaptera novaeangliae ) as a model species and collected blow and control samples in August 2016 and 2017 for an interannual comparison. We analysed the blow by barcode tag sequencing of the bacterial 16S rRNA gene. We found that the microbial communities in 2016 and 2017 were statistically similar regarding alpha and beta diversity but distinct to seawater. Zero-radius operational taxonomic units (zOTUs) shared by both groups accounted for about 50% of all zOTUs present. Still, the large individual variability in the blow microbiota resulted in a small number of core taxa (defined as present in at least 60% of whales). We conclude that the blow microbiota of humpback whales is either generally limited and of transient nature or the reduced airway microbiota is the symptom of a compromised physiological state potentially due to the challenges of the whales' annual migration. Abstract : This study investigated composition and core of whale blow and seawater microbiota through an interannual analysis of blow samples of humpback whales and seawater at the East Coast of Australia.